Model Pembelajaran Bahasa Arab Berbasis Pendekatan Bermain dan Kontekstual pada Anak Usia Dini: Studi Kualitatif di Lembaga Pendidikan Islam - Ima Rohimah; Ediat Ediat (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Arabic language learning in early childhood education plays a crucial role in introducing linguistic and religious literacy from an early stage. However, its implementation in Islamic early childhood institutions often faces challenges related to instructional methods, teacher competence, and limited learning resources. This study aims to analyze the implementation model of Arabic language learning within an Islamic early childhood education context. Employing a qualitative case study design, data were collected through participant observation, in-depth interviews, and documentation analysis. The findings indicate that Arabic language learning is implemented through play-based and contextual approaches, including singing, role-playing, and thematic vocabulary integration. The use of visual and audiovisual media, such as flashcards and animated videos, enhances children's engagement and comprehension. In addition to qualitative insights, supporting documentation of learning outcomes suggests an observable improvement in students’ language abilities over the course of instruction, reflected in classroom-based assessments. The study further identifies supporting factors such as students’ motivation and teacher creativity, alongside challenges including time constraints, varying learner abilities, and limited parental involvement. Based on these findings, the study proposes an integrative pedagogical model that combines play-based learning, contextual learning, and principles of natural language acquisition to support more effective Arabic language learning in early childhood education within Islamic settings.